Dopuszczalność pozyskiwania danych osobowych pracowników przez pracodawców na przykładzie zaświadczeń o niekaralności - Kawecki, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In the jurisprudence and the professional literature, consistently controversial is the question of the legal basis for the processing of personal data of employees by employers, including certificates of no criminal record. Particularly problematic is the admissibility of receiving consent from the employees to processing of their personal data. The aim of the article is to indicate existing in this context judicial and doctrinal opinions, and an indication of the correct, in the opinion of the author, interpretation of legislation. Particularly criticized should be the position of GIODO which excludes the possibility of receiving consent from employees to the processing of their data, which is not only a violation of their constitutionally guaranteed autonomy of information, but is also contrary to the literal interpretation of the legal rules.
Keywords: pracownik; dane osobowe; przetwarzanie danych osobowych